Cardioprotective Actions of the Annexin-A1 N-Terminal Peptide, Ac2-26, Against Myocardial Infarction - Qin, Cheng Xue; Rosli, Sarah; Deo, Minh; Cao, Nga; Walsh, Jesse; Tate, Mitchel; Alexander, Amy E.; Donner, Daniel; Horlock, Duncan; Li, Renming; Kiriazis, Helen; Lee, Man K. S.; et al. (Frontiers in Pharmacology, 2019)
The anti-inflammatory, pro-resolving annexin-A1 protein acts as an endogenous brake against exaggerated cardiac necrosis, inflammation, and fibrosis following myocardial infarction (MI) in vivo. Little is known however regarding the cardioprotective actions of the N-terminal-derived peptide of annexin A1, Ac2-26, particularly beyond its anti-necrotic actions in the first few hours after an ischemic insult. In this study, we tested the hypothesis that exogenous Ac2-26 limits cardiac injury in vitro and in vivo. Firstly, we demonstrated that Ac2-26 limits cardiomyocyte death both in vitro and in mice subjected to ischemia-reperfusion (I-R) injury in vivo (Ac2-26, 1 mg/kg, i.v. just prior to post-ischemic reperfusion). Further, Ac2-26 (1 mg/kg i.v.) reduced cardiac inflammation (after 48 h reperfusion), as well as both cardiac fibrosis and apoptosis (after 7-days reperfusion). Lastly, we investigated whether Ac2-26 preserved cardiac function after MI. Ac2-26 (1 mg/kg/day s.c., osmotic pump) delayed early cardiac dysfunction 1 week post MI, but elicited no further improvement 4 weeks after MI. Taken together, our data demonstrate the first evidence that Ac2-26 not only preserves cardiomyocyte survival in vitro, but also offers cardioprotection beyond the first few hours after an ischemic insult in vivo. Annexin-A1 mimetics thus represent a potential new therapy to improve cardiac outcomes after MI.